2015
DOI: 10.1073/pnas.1414055112
|View full text |Cite
|
Sign up to set email alerts
|

SK3 channel and mitochondrial ROS mediate NADPH oxidase-independent NETosis induced by calcium influx

Abstract: Neutrophils cast neutrophil extracellular traps (NETs) to defend the host against invading pathogens. Although effective against microbial pathogens, a growing body of literature now suggests that NETs have negative impacts on many inflammatory and autoimmune diseases. Identifying mechanisms that regulate the process termed “NETosis” is important for treating these diseases. Although two major types of NETosis have been described to date, mechanisms regulating these forms of cell death are not clearly establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
664
2
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(706 citation statements)
references
References 46 publications
26
664
2
14
Order By: Relevance
“…This cellular process requires the generation of ROS (38, 42, 53). However, ROS-mediated signaling is not the only way that NET release is triggered, as rapid NET formation (within minutes) was described, which is independent of oxidants (41,54). Our present study shows that S. aureus triggers the formation of NETs through a mechanism that does not depend on ROS.…”
Section: Discussionmentioning
confidence: 45%
“…This cellular process requires the generation of ROS (38, 42, 53). However, ROS-mediated signaling is not the only way that NET release is triggered, as rapid NET formation (within minutes) was described, which is independent of oxidants (41,54). Our present study shows that S. aureus triggers the formation of NETs through a mechanism that does not depend on ROS.…”
Section: Discussionmentioning
confidence: 45%
“…ROS: Reactive oxygen species. that NETs can be formed by more than one process [71][72][73][74]. The 'classic' mechanism of NET formation involves death of the neutrophil (recently termed 'suicidal NETosis').…”
Section: • Composition Of Netsmentioning
confidence: 99%
“…A second, NADPH oxidaseindependent, calcium-mediated NETosis pathway has also been described, involving the enzyme, protein arginine deiminase 4 (PAD4) (4). Upon the increase of intracellular calcium in response to agents such as calcium ionophores, PAD4 binds calcium, crosses into the nucleus, and deiminates positively charged arginine residues to generate uncharged citrullin on histones H3 and H4.…”
Section: What Are Neutrophil Extracellular Traps?mentioning
confidence: 99%
“…This loss of positive charge leads to the dissociation of the histones from negatively charged DNA, resulting in decondensation of the nucleosome. Citrullination of histones has been shown to be involved in calcium-dependent, but not NADPH oxidase-dependent, NETosis (4). It was demonstrated that PAD4 deficiency or use of Cl-amidine to chemically inhibit PAD4 activity causes a reduction of histone decondensation and NET formation (5).…”
Section: What Are Neutrophil Extracellular Traps?mentioning
confidence: 99%